The Understanding of Peak Oxygen Uptake in Children Aged 8–16 - Wong, Simpson W. L.; Yu, Clare C. W.; Li, Albert M. (Frontiers in Pediatrics, 2021)
Objective: To examine the understanding of concept peak oxygen consumption (VO2) from a developmental perspective among children at different ages. Methods: A total of 549 children and adolescents aged 8 to 16 were recruited and instructed to fill in a peak VO2 understanding inventory asking the resulting volume of peak VO2 under different circumstances. The inventory included 20 items, and was developed with reference to research literature on peak VO2. Each item of the inventory presented the participants with a scenario, and they were asked to indicate whether VO2 would “remain unchanged,” “increase,” or “decrease,” or that there was “insufficient information for a definite answer.” The cross-sectional data was analyzed by employing a series of ANOVA analyses and chi-square association tests. Results: Except for the 8-year-old group, the overall accuracy rate did not improve with age. Age-related differences in the choice of answers (“increase”’, “decrease”, “unchanged”, and “uncertain”) for determining the resulting peak VO2 after a change of antecedent were observed. Item analysis showed that prefactual thinking that is important to understand the concept is emerging rather than fully developed in our child and adolescent samples. Conclusion: The mastery of peak VO2 is not subject to age-related maturation but demand specific logical reasoning skill such as perfactual thinking. Early introduction of peak VO2 and health-related concepts is advocated and should be emphasized on the reasoning rather than providing model answers in health literacy education.